2014
DOI: 10.1371/journal.pntd.0003008
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis as an Emerging Threat in Developing Economies: Lessons from Nigeria

Abstract: Nigeria is the most populous country in Africa, has a large proportion of the world's poor livestock keepers, and is a hotspot for neglected zoonoses. A review of the 127 accessible publications on brucellosis in Nigeria reveals only scant and fragmented evidence on its spatial and temporal distribution in different epidemiological contexts. The few bacteriological studies conducted demonstrate the existence of Brucella abortus in cattle and sheep, but evidence for B. melitensis in small ruminants is dated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
143
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 63 publications
5
143
1
2
Order By: Relevance
“…Since then, the disease has continued to devastate both humans and animals in the country; causing enormous economic losses in animal agriculture [11] and significant health problems in humans [3,12,13], especially among individuals occupationally exposed to brucellosis. About 90% of global brucellosis cases occur in resource-limited developing countries or tropical climatic regions of the world [14,15]; where livestock production is incidentally a major means of livelihood [10,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the disease has continued to devastate both humans and animals in the country; causing enormous economic losses in animal agriculture [11] and significant health problems in humans [3,12,13], especially among individuals occupationally exposed to brucellosis. About 90% of global brucellosis cases occur in resource-limited developing countries or tropical climatic regions of the world [14,15]; where livestock production is incidentally a major means of livelihood [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis in animals is transmitted through coitus or use of infected semen during artificial insemination, inhalation of aerosolized Brucella agents, ingestion of tissues or discharges from infected animals, in vivo or in vitro maternal transfer to fetus, and lactation by infected dam [14][15][16][17]. In livestock, the disease manifests as middle or late-term abortion, birth of unthrifty neonates, retained placenta, reduced milk yield, repeat breeder syndrome, increased parturition interval, lameness due to polyarthritis, orchitis, and epididymitis in males [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is a highly contagious, zoonotic and economically important bacterial disease worldwide that causes significant economic losses from abortion, reduced milk production, low fertility rates and increased cost of replacing cattle (Ducrotoy et al, 2014). It is one of the most important zoonotic diseases in the world as it can impact human health either through direct contact with infected animals or through the consumption of contaminated milk as well as dairy products and it has the potential to also affect animal health (Muhammad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine brucellosis is recognized as an important potential zoonoses in developing countries (McDermott et al, 2013;Ducrotoy et al, 2014). Recently, the World Health Organization has declared brucellosis to be a significant re-emerging zoonoses (World Health Organization [WHO], 2004;Seleem et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine brucellosis was initially reported in 1927 but first recorded in Nigeria around 1928 (Ducrotoy et al, 2014), while the first case in Southwest Nigeria was reported in 1965 (Ducrotoy et al, 2014). Prevalence of bovine brucellosis between 0.2 and 80% across the different regions of Nigeria as well as between herds have been reported by various authors and summarized by Ducrotoy et al (2014), while institutional and abattoir prevalence between 3.7 and 48.8% have been reported in the Southern part of Nigeria (Cadmus et al, 2010(Cadmus et al, , 2013).…”
Section: Introductionmentioning
confidence: 99%